TOPOGRAPHICAL AND TECHNO-ECONOMIC ASSESSMENT OF UTILITY-SCALE SOLAR PV DEVELOPMENT IN LEDEK MOUNTAIN, CENTRAL JAVA, INDONESIA - Qudus, Nur; Aprilianto, Rizky Ajie; Yuhanafia, Nurul; Anita, Nur; Budi, Listiyono (Veredas do Direito, 2025)
This study conducts an integrated topographical and techno-economic assessment of a proposed utility-scale solar photovoltaic (PV) power plant at Ledek Mountain, Central Java, Indonesia. The research aims to evaluate site feasibility, economic performance, and sustainability potential within the Universitas Negeri Semarang (UNNES) Science and Techno Park, an area promoting conservation-based innovation. A drone-based photogrammetric and GIS survey identified 27 hectares of suitable land, supporting an installed capacity of 18 MWp. The system, optimized for local climatic conditions, produces an annual energy yield of 25,229 MWh with a performance ratio of 80%. The techno-economic analysis estimates a total project cost of USD 19.09 million and a Levelized Cost of Energy (LCOE) of USD 0.030/kWh—well below Indonesia’s average tariff. The project is projected to generate USD 31.5 million in revenue with a 65% ROI and a 16.9-year payback period. Sensitivity analysis confirms economic resilience to variations in module cost, electricity price, and discount rate. With an annual output sufficient to power 194,000 households or 25,000 small industries, the project demonstrates significant social and environmental benefits. Beyond its technical merits, the initiative illustrates the pivotal role of universities in accelerating renewable energy integration and advancing the Sustainable Development Goals (SDGs) 7 and 13 through sustainable land-use and institutional planning.